2011
DOI: 10.4414/smw.2011.13172
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, clinical presentation and imaging findings of cavernous malformations of the CNS. A twenty-year experience

Abstract: The observed frequency of CM, including multiple lesions in a single individual and the familial form of this pathological entity appears relatively high compared to medical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
(47 reference statements)
0
13
0
1
Order By: Relevance
“…The lesions gener ally present as single lesions, but they can also be multiple lesions. Moreover, in the literature, it has been reported that some cases have inherited CH from family members (8,9).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The lesions gener ally present as single lesions, but they can also be multiple lesions. Moreover, in the literature, it has been reported that some cases have inherited CH from family members (8,9).…”
Section: Introductionmentioning
confidence: 97%
“…In bleeding cases, the appearance of popcorn is typical (1). A hemosiderin-stained gliotic layer, associated with chronic slight bleedings, surrounds the lesion (9). In computed tomography (CT), CHs are generally seen as iso /h y p o d e n se .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although almost all of the cases have micro-bleedings, bleeding leading to clinical symptoms is a rare entity in cavernomas (0,25-6%) (6). Symptoms are reported to occur when the lesion diameter is greater than 1,75 cm (7). Cavernous malformations are found in the cerebral hemispheres (66%), brainstem A neurosurgical intervention was performed and consisted of a left frontal craniotomy, with a left-sided transcallosal approach.…”
Section: Patientmentioning
confidence: 99%
“…4,5 Magnetic resonance imaging (MRI) has dramatically increased the detection rate and apparent prevalence and morbidity of intracranial cavernous haemangiomas. 6 Parasellar meningiomas and cavernous haemangiomas are often indistinguishable on conventional T 1 and T 2 -weighted imaging sequences. 1 As parasellar cavernous haemangiomas are rare, they are frequently misdiagnosed as meningiomas and subsequently resected, 1 but correct preoperative diagnosis allows for more appropriate treatment (radiation therapy rather than surgical resection).…”
Section: Introductionmentioning
confidence: 99%